The RasGEF FgCdc25 regulates fungal development and virulence in Fusarium graminearum via cAMP and MAPK signalling pathways. (15th July 2020) - Chen, Ahai; Ju, Zhenzhen; Wang, Jinli; Wang, Jing; Wang, Hongkai; Wu, Jiayu; Yin, Yanni; Zhao, Youfu; Ma, Zhonghua; Chen, Yun
Summary: Ras GTPases act as molecular switches to control various cellular processes by coupling integrated signals in eukaryotes. Activities of Ras GTPases are triggered by Ras GTPase guanine nucleotide exchange factors (RasGEFs) in general, whereas the role of RasGEF in plant pathogenic fungi is largely unknown. In this study, we characterized the only RasGEF protein in Fusarium graminearum, FgCdc25, by combining genetic, cytological and phenotypic strategies. FgCdc25 directly interacted with RasGTPase FgRas2, but not FgRas1, to regulate growth and sexual reproduction. Mutation of the FgCDC25 gene resulted in decreased toxisome formation and deoxynivalenol (DON) production, which was largely depended on cAMP signalling. In addition, FgCdc25 indirectly interacted with FgSte11 in FgSte11‐Ste7‐Gpmk1 cascade, and the Δ Fgcdc25 strain totally abolished the formation of infection structures and was nonpathogenic in planta, which was partially recovered by addition of exogenous cAMP. In contrast, FgCdc25 directly interplayed with FgBck1 in FgBck1‐MKK1‐Mgv1 cascade to negatively control cell wall integrity. Collectively, these results suggest that FgCdc25 modulates cAMP and MAPK signalling pathways and further regulates fungal development, DON production and plant infection in F. graminearum .